2018
DOI: 10.1097/md.0000000000009570
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture perceptions in the college of dentistry

Abstract: A positive safety culture is essential to patient safety because it improves quality of care. The aim of this study was to assess staff and student perceptions of the patient safety culture in the clinics of the College of Dentistry at King Saud University in Saudi Arabia.A cross-sectional study was conducted in the College of Dentistry at King Saud University in Saudi Arabia. It included 4th and 5th year students, interns, general practitioners, and dental assistants. The data were collected by using paper-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…Therefore, a modest understanding of PS might affect the effectiveness of hospital delivery services. Similarly, an average PS perception result replicated this pattern in previous studies in Saudi Arabia (Al Sweleh, Al Saedan, & Al Dayel, ; Alquwez et al, ) and Germany (Sendlhofer, Wolfler, & Pregartner, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, a modest understanding of PS might affect the effectiveness of hospital delivery services. Similarly, an average PS perception result replicated this pattern in previous studies in Saudi Arabia (Al Sweleh, Al Saedan, & Al Dayel, ; Alquwez et al, ) and Germany (Sendlhofer, Wolfler, & Pregartner, ).…”
Section: Discussionsupporting
confidence: 84%
“…As indicated in Table 4, working hours per week and staff position were identified as significant predictors. Specifically, healthcare workers working for less than 40 hr per week (β = −0.26, p < .001, 95% CI = −0.37, −0.14) and more than 60 hr per week (β = −0.25, p = .001, 95% CI = −0.39, & Al Dayel, 2018;Alquwez et al, 2018) and Germany (Sendlhofer, Wolfler, & Pregartner, 2015).…”
Section: Work-related Predictorsmentioning
confidence: 99%
“…Some might speculate that it is too early to question students of dental hygiene and dental sciences about their perceptions of managerial support. In a similar previous study, students of dentistry reported highly positive perceptions of ‘organizational learning’, ‘continuous improvement’ and ‘teamwork’ [ 38 ]. Although after graduation most dentists work independently at private clinics, this is not the case with dentists employed in healthcare facilities.…”
Section: Discussionmentioning
confidence: 90%
“…They are eager to learn and work, and regularly receive support from other members of staff. It was reported that after graduation and employment, the perceptions of the culture of patient safety among graduates of dental professionals’ improves further [ 38 ]. Therefore, this stage is critical: students placed in clinical training environments where there is a lack of support often lag behind in terms of skill development, and may even withdraw from education [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient safety culture means the beliefs, values, and standards shared by professionals and that also influence their behaviors and actions 63 . In the course of this review, studies alluded to the theme 13,64,65 or used it as their central focus 47,61,66,67,68,69,70,71,72,73 . Positive points were found, such has a high overall perception of patient safety; patient-centered care; the pursuit of effective and equitable care; and the value assigned to teamwork.…”
Section: The Problem's Size and Understanding Its Causesmentioning
confidence: 99%